Analysis of Lead (PB) Metal Content in Soil and Peanut Seeds Arachis hypogaea With the Application of Coal Ash Fly Ash and Bottom Ash (FABA) in Post-Tin Mining Land - Nyayu Siti Khodijah; Ismed Inonu; Deni Pratama; Occa Roanisca; Muhammad Fauzan Ridho; Nyayu Siti Khodijah (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2026)
The increase of heavy metal content in post-mining land is one of the main challenges in using tin mine tailings for agricultural activities. This study aimed to determine lead changes (Pb) concentrations in tin mine tailings after the application of Faba (fly ash–bottom ash) and the cultivation of peanut (Arachis hypogaea L.), and to evaluate the potential for Pb accumulation in peanut seeds. The experiment was conducted using five levels of Faba application (0; 15; 30; 45; and 60 tons/ha) on tin mine tailings, followed by peanut cultivation for one growing season. The results showed that Faba application increased total soil Pb concentration from 0.09 mg/kg (without Faba) to 19.58 mg/kg (60 tons/ha). However, after peanut cultivation, soil Pb content in all treatments decreased to below the AAS detection limit (< 8.73 mg/kg). Analysis of peanut seeds revealed that Pb levels were also below the detection limit (< 0.165 mg/kg), indicating no significant Pb accumulation in the seeds. This study demonstrates that applying Faba at certain doses can modify the chemical characteristics of mine tailings, and that peanut cultivation has the potential to reduce soil Pb levels through absorption and immobilization mechanisms. The key finding of this study is that combining Faba application at 30–45 tons/ha with peanut cultivation effectively reduces soil Pb content without increasing contamination in harvested seeds. Furthermore, peanut seeds remain safe for consumption due to their very low Pb concentration. Therefore, integrating Faba-based amelioration with the cultivation of excluder or phytoremediation plants, such as peanuts, is recommended as an environmentally friendly tailings reclamation strategy that supports sustainable food security.